Evaluation of bioactivities of tamarindus indica and the effects of the antioxidant-rich extracts on the transcriptome profiles in liver hepg2 cells / Nurhanani Razali - Nurhanani, Razali (2015)
Tamarindus indica L. (T. indica) or locally known as “asam jawa”, belongs to the family Leguminosae and grows naturally in many tropical and sub-tropical regions. In this study, the antioxidant activities of T. indica leaf, seed, vein and skin extracted with methanol, ethyl acetate and hexane were investigated. In addition, the effects of the antioxidant-rich crude and fractionated extracts of T. indica on lipid peroxidation, antioxidant enzyme activities and gene expression patterns were investigated in liver HepG2 cells. Amongst the various parts of T. indica, the methanol leaf and seed extracts showed high phenolic content and antioxidant activities. The crude methanol extracts of T. indica leaf and seed were subjected to bioactivity-guided fractionation. Fraction 10 (F10) and fraction 3 (F3), obtained from the methanol leaf and seed extracts, respectively, showed the highest phenolic content and antioxidant activities. When treated on HepG2 cells, F10 and F3 exhibited potent cytotoxic effect and antioxidant activities and were able to inhibit lipid peroxidation and enhanced superoxide dismutase, catalase and glutathione peroxidase activities. Overall, fractionation of the methanol leaf and seed extracts gave higher phenolic content, antioxidative protection and cytotoxicity compared to the respective crude extracts. Amongst all extracts, F10 showed the most potent antioxidant activities. Analyses of polyphenols in the methanol leaf extract using UHPLC revealed the presence of gallic acid, epicatechin, caffeic acid, p-coumaric acid, ferulic acid, ellagic acid, quercetin, apigenin, isorhamnetin and an unknown compound. UHPLC analyses of the methanol seed extract revealed the presence of catechin, procyanidin B2, caffeic acid, ferulic acid, chloramphenicol, myricetin, morin, quercetin, apigenin and iv kaempferol. NMR analyses characterised F3 as caffeic acid, while a novel compound was identified in F10. cDNA microarray analysis revealed that 207 genes were significantly regulated by at least 1.5-fold (p < 0.05) in leaf-treated HepG2 cells. When the significantly regulated genes were analysed using Ingenuity Pathway Analysis (IPA) software, “Lipid Metabolism, Small Molecule Biochemistry, Hematological Disease’ was the top network affected by the leaf extract, with a score of 36. The top predicted canonical pathway affected by the leaf extract was the coagulation system (P < 2.80 x 10-6) involving five genes namely KNG1, SERPINC1, SERPIND1, SERPINE1, FGG, FGA. In seed-treated HepG2 cells, 167 genes were significantly up-regulated while 80 genes were down-regulated in response to the IC20 treatment. IPA analyses showed that “Free Radical Scavenging, Hematological System Development and Function, Inflammatory Response” was the top network affected by the seed extract, with a score of 45. The top predicted canonical pathway affected by the seed extract was the NRF2-mediated oxidative stress response (P < 2.84 x 10-9) involving 10 genes namely AKT1, DNAJC10, GPX2, GSTA4, MAPK8, MGST2, PTPLAD1, SOD1, TXNRD1, USP14. Similar pattern of expression was observed for selected proteins. The promising therapeutic potency of T. indica particularly the leaves and the seeds reported in this study implies the potential of this plant as an alternative source of natural antioxidant agent. This study also provides further scientific evidence to support the medicinal uses of this plant.